Institutional reforms and agricultural policy process: lessons from Democratic Republic of Congo - Ragasa, Catherine; Babu, Suresh Chandra; Ulimwengu, John M. (Springer, 2014)
Attaining food security for all requires well-functioning institutions and policy process that are effective in designing and implementing food and agricultural policies and programs. This paper assesses early stages of the decentralization and institutional reforms in the policymaking processes in the Democratic Republic of Congo (DRC). It develops a conceptual framework and adopts an innovative mapping tool to identify capacity and incentive challenges impeding the effective design and implementation of food and agricultural policy and institutional reform processes. We found that decentralized platforms for policy dialogues have the potential to improve civil society participation in local-level and national-level policy and planning processes. However, their success depends on organizational and human capacity strengthening, financial sustainability, effective participation of the civil society, and demonstrated impact of their participation. D72; D74; D78; Q18